A ceramic-hybrid resin-based gradient heat-insulating integrated composite material and preparation method thereof
By immersing the silicon-containing ceramic precursor on the side of the silicon carbide fiber and performing alternating pressure immersion, combined with the single-sided muffle furnace heating method, a ceramic-hybrid resin-based gradient heat-proof and insulation integrated composite material is prepared, which solves the problem that traditional materials are difficult to have both ablation resistance and long-term heat insulation, and achieves the effect of having multiple functions under a single structure.
Patent Information
- Application Number
- CN202311469578.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-11-07
AI Technical Summary
Traditional resin-based or ceramic-based composite materials are difficult to have both ablation resistance and long-term thermal insulation properties, and cannot meet the heat protection needs of spacecraft with high Mach long-term flight characteristics.
A ceramic-hybrid resin-based gradient anti-insulation integrated composite material is used to immerse the silicon-containing ceramic precursor on the side of the silicon carbide fiber and perform alternating pressure immersion, and combined with a single-sided muffle furnace heating method, a ceramic-hybrid resin-based material with a gradient structure is prepared.
It achieves both ablation resistance and long-term thermal insulation properties under a single structure, and is suitable for spacecraft thermal protection materials, improving the ablation resistance of the material and reducing thermal conductivity.
Smart Images

Figure CN117510228B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal protection materials, and in particular to a ceramic-hybrid resin-based gradient heat-insulating integrated composite material and a preparation method thereof. Background Art
[0002] Resin-based composite materials are widely used thermal protection materials for aerospace vehicles. However, resin-based thermal protection materials have a low service temperature and poor ablation resistance, and cannot meet the thermal protection requirements of spacecraft with high Mach long-term flight characteristics. Although ceramic-based composite materials have high temperature resistance and excellent ablation resistance, their thermal conductivity is relatively high, which seriously affects their long-term thermal insulation performance. Therefore, a single resin-based composite material or ceramic-based composite material is difficult to meet the thermal insulation requirements of aerospace vehicles with gradually increasing flight speeds. Therefore, the development of new ablation-resistant and long-term thermal insulation integrated materials is an urgent need in this field. Summary of the invention
[0003] The purpose of the present invention is to provide a ceramic-hybrid resin-based gradient heat-insulating integrated composite material and a preparation method thereof.
[0004] The objective of the present invention can be achieved by the following technical scheme: a method for preparing a ceramic-hybrid resin-based gradient heat-insulating integrated composite material, wherein an organosilicon hybrid resin added with a pore-forming solvent is injected into a fiber preform of a silicon carbide-quartz gradient woven structure, and cured to obtain a porous resin-based composite material, a silicon-containing ceramic precursor is immersed from the silicon carbide fiber side of the porous resin-based composite material, and cured to obtain a gradient resin-based composite material, and the silicon carbide fiber side of the gradient resin-based composite material is heated to prepare a ceramic-hybrid resin-based gradient heat-insulating integrated composite material.
[0005] The organosilicon hybrid resin contains a large amount of silicon elements. The porous resin formed after curing has good chemical compatibility with the silicon-containing ceramic precursor, which is more conducive to the full impregnation of the silicon-containing ceramic precursor. In addition, the organosilicon hybrid resin can react with the silicon-containing ceramic precursor in situ at high temperature to generate silicon-containing ceramics, thereby improving the surface ceramicization yield.
[0006] Preferably, the organosilicon hybrid resin includes organosilicon hybrid phenolic resin, organosilicon hybrid epoxy resin, and organosilicon hybrid polyimide resin.
[0007] Preferably, the types of pore-forming solvents include but are not limited to organic solvents with a boiling point of about 80° C., such as ethanol, ethyl acetate, and isopropanol.
[0008] Preferably, the volume of the pore-forming solvent accounts for 25% to 35% of the total volume of the organosilicon hybrid resin and the pore-forming solvent.
[0009] The organic solvent with a boiling point of about 80°C can gradually volatilize during the curing process at 75-85°C, so that the cured resin forms a porous structure, which is beneficial to the impregnation of silicon-containing ceramic precursors and also helps to reduce the thermal conductivity of the ceramic-hybrid resin-based gradient heat-insulating integrated composite material. The pore-forming solvent with a volume content of 25% to 35% can make the cured resin form 25% to 35% pores. The pores with this volume fraction can make the composite material have both good mechanical properties and thermal insulation properties.
[0010] Preferably, the silicon carbide-quartz gradient braided structure consists of a silicon carbide fiber layer, an intermediate transition layer comprising silicon carbide fibers and quartz fibers, and a quartz fiber layer.
[0011] Preferably, the silicon carbide-quartz gradient braided structure includes a 2.5D braided structure, an orthogonal three-way braided structure, and a three-dimensional four-way braided structure.
[0012] Preferably, the volume percentage of the silicon carbide fiber layer decreases in proportion from 95% to 100% to 5% to 0% in the thickness direction, and at the same time, the volume percentage of the quartz fiber layer increases in proportion from 5% to 0% to 95% to 100% in the thickness direction, and the gradient of the decrease in the volume fraction of the silicon carbide fiber layer is the same as the gradient of the increase in the volume fraction of the quartz fiber layer.
[0013] Silicon carbide fiber preforms have excellent ablation resistance, but high thermal conductivity. Quartz fiber has lower thermal conductivity, but poor ablation resistance. Therefore, designing a silicon carbide-quartz fiber gradient structure can make the surface of the composite material have excellent ablation resistance, while showing lower thermal conductivity as a whole. In addition, the fiber preform with a woven structure has higher ablation resistance and mechanical properties than the needle-punched structure preform, which is beneficial to improve the reliability of the composite material.
[0014] Preferably, an organosilicon hybrid resin added with a pore-forming solvent is injected into a fiber preform of a silicon carbide-quartz gradient woven structure through an alternating vacuum-assisted RTM process, and the injected resin is cured through an alternating temperature curing process to obtain a porous resin-based composite material.
[0015] By using a vacuum value that alternates at a certain amplitude and frequency, the resin can be more evenly filled into the pores of the fiber preform, which is beneficial to improving the ablation resistance of the composite material. By using a curing temperature that alternates at a certain amplitude and frequency, the resin can be cured more fully, which is more beneficial to improving the ablation resistance of the material.
[0016] Further preferably, in the alternating vacuum-assisted RTM process, the internal pressure of the resin container is 0.2 to 1.0 MPa, the vacuum value of the vacuum pump is not a constant value but an alternating value, the set vacuum value is -0.08 to -0.95 MPa, the alternating amplitude is 4% to 9% of the set vacuum value, and the alternating frequency is 0.2 to 0.6 Hz.
[0017] Further preferably, in the alternating temperature curing process, the temperature during the curing process is not a constant value, but an alternating temperature. The curing temperature is set to 75-85°C, the alternating temperature amplitude is 1%-3% of the set curing temperature value, the alternating frequency is 0.02-0.08Hz, and the curing time is 24-36h.
[0018] Preferably, the specific process of infiltrating the silicon-containing ceramic precursor from the silicon carbide fiber side of the porous resin-based composite material comprises the following steps:
[0019] S1: The surface of the silicon carbide fiber side of the porous resin-based composite material is exposed, and the other surfaces are sealed with a vacuum bag, placed in a closed container, and the silicon-containing ceramic precursor is impregnated into the porous resin-based composite material by an alternating pressure impregnation process;
[0020] S2: setting the curing temperature to 110-130° C., fully curing the immersed silicon-containing ceramic precursor for 6-12 hours, and obtaining a gradient resin-based composite material.
[0021] Only by impregnating the silicon-containing ceramic precursor on the surface of the silicon carbide fiber side, the ablation resistance of the material can be improved without affecting the thermal conductivity and density of the overall material. The alternating pressure impregnation process is more conducive to the ceramic precursor entering the porous resin-based composite material, thereby improving the ablation resistance of the material.
[0022] Further preferably, the silicon-containing ceramic precursor includes polycarbosilane, polysilazane, or polysiloxane.
[0023] Further preferably, in the alternating pressure impregnation process, the set pressure value is 2-3 MPa, the alternating amplitude is 2-10% of the set pressure value, the alternating frequency is 0.2-1.0 Hz, and the impregnation time is 10-20 h.
[0024] Preferably, a single-sided muffle furnace heating method is used to heat the silicon carbide fiber side of the gradient resin-based composite material.
[0025] A single-sided muffle furnace with an open hearth is used to heat the resin-based composite material, so that the side that needs to be ceramicized can be fully heated, while the other side is exposed to the air and is not affected by the thermal environment.
[0026] More preferably, the heating temperature of the single-sided muffle furnace is 900-1200° C., and the heating time is 1-2 hours.
[0027] The ceramic precursor on the side surface of the silicon carbide fiber of the gradient resin-based composite material is completely ceramicized, and the internal ceramic precursor is gradient ceramicized, so as to prepare a ceramic-hybrid resin-based gradient heat-insulating integrated composite material.
[0028] A ceramic-hybrid resin-based gradient heat-insulating integrated composite material is prepared by adopting the preparation method.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention solves the problem that traditional thermal protection resin-based or ceramic-based composite materials cannot have both ablation resistance and long-term thermal insulation properties.
[0031] 2. The material of the present invention can achieve multiple functions such as ablation resistance and long-term heat insulation under a single structure, and can be applied to thermal protection materials of aerospace vehicles.
[0032] 3. The present invention selects organosilicon hybrid resin as the matrix raw material. The organosilicon hybrid resin contains a large amount of silicon elements. The porous resin formed after curing has good chemical compatibility with the silicon-containing ceramic precursor, which is more conducive to the full impregnation of the silicon-containing ceramic precursor. In addition, the organosilicon hybrid resin can react with the silicon-containing ceramic precursor in situ at high temperature to generate silicon-containing ceramics, thereby improving the surface ceramic yield.
[0033] 4. The present invention only immerses the silicon-containing ceramic precursor on the surface of the silicon carbide fiber side, which can improve its ablation resistance without affecting the thermal conductivity and density of the overall material. The alternating pressure impregnation process is more conducive to the ceramic precursor entering the porous resin-based composite material, thereby improving the ablation resistance of the material.
[0034] 5. The present invention uses a single-sided muffle furnace heating method to heat only the side of the material that needs to be ceramicized, so that the ceramic precursor on the surface is completely ceramicized, while the resin-based composite material on the other side is not affected by the temperature, thereby facilitating the preparation of a ceramic-hybrid resin-based gradient heat-insulating integrated composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of the principle of the single-sided muffle furnace heating method of the present invention;
[0036] Figure 2 It is a schematic structural diagram of the ceramic-hybrid resin-based gradient heat-insulating integrated composite material of the present invention;
[0037] In the figure: 1-silicon-containing ceramic matrix, 2-silicon carbide fiber, 3-ceramic / resin gradient matrix, 4-quartz fiber, 5-organosilicon hybrid resin matrix. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0039] A ceramic-hybrid resin-based gradient heat-insulating integrated composite material and a preparation method thereof, the method comprising the following steps:
[0040] S1: Selecting organic silicon hybrid resin as the matrix raw material, adding a pore-forming solvent with a boiling point of about 80°C, and selecting a fiber preform of a silicon carbide-quartz gradient woven structure as the reinforcement;
[0041] S2: injecting resin into the fiber preform through an alternating vacuum-assisted RTM process, and curing the injected resin through an alternating temperature curing process to obtain a porous resin-based composite material;
[0042] S3: The silicon-containing ceramic precursor is impregnated from the silicon carbide fiber side of the porous resin-based composite material through alternating pressure impregnation to form a gradient structure with high surface content and low internal content, and is fully cured to obtain a gradient resin-based composite material;
[0043] S4: A single-sided muffle furnace heating method is used to heat the silicon carbide fiber side of the gradient resin-based composite material, so that the surface ceramic precursor is completely ceramicized and the internal ceramic precursor is gradient ceramicized, thereby preparing a ceramic-hybrid resin-based gradient thermal insulation integrated composite material.
[0044] The following describes it in detail with reference to specific embodiments.
[0045] Example 1
[0046] Step 1. Select an organosilicon hybrid phenolic resin as a resin matrix raw material, and the organosilicon hybrid phenolic resin is prepared according to patent ZL201911266938.7.
[0047] Step 2. Ethanol is selected as the pore-forming solvent, and its volume content accounts for 25% of the total volume of the resin and the pore-forming solvent.
[0048] Step 3. Select a fiber preform of a silicon carbide-quartz gradient 2.5D woven structure as a reinforcement. The silicon carbide fiber-quartz fiber gradient structure consists of a silicon carbide fiber layer, an intermediate transition layer containing both silicon carbide fiber and quartz fiber, and a quartz fiber layer. The volume percentage of the silicon carbide fiber layer decreases in a proportional gradient from 95% to 5% in the thickness direction. At the same time, the volume percentage of the quartz fiber layer increases in a proportional gradient from 5% to 95% in the thickness direction. And the gradient of the reduction in the volume fraction of the silicon carbide fiber layer is the same as the gradient of the increase in the volume fraction of the quartz fiber layer.
[0049] Step 4: Using alternating vacuum-assisted RTM process, setting the vacuum value to -0.08 MPa, the alternating amplitude to 4%, the alternating frequency to 0.2 Hz, and injecting resin into the fiber preform.
[0050] Step 5. Use the alternating temperature curing process to cure the resin, set the curing temperature to 75°C, the alternating temperature amplitude to 1% of the set curing temperature value, and the alternating frequency to 0.02 Hz. The curing time is 24 hours. After curing, a porous resin-based composite material is obtained.
[0051] Step 6. Select polycarbosilane as the silicon-containing ceramic precursor, expose the surface of the silicon carbide fiber side of the porous resin-based composite material, seal the other surfaces with a vacuum bag, place it in a closed container, and use an alternating pressure impregnation process to impregnate the polycarbosilane into the porous resin-based composite material. The pressure value of the alternating pressure impregnation is 2MPa, the alternating amplitude is 2% of the set pressure value, the alternating frequency is 0.2Hz, and the impregnation time is 10h.
[0052] Step 7. Set the curing temperature to 110° C. and the curing time to 6 h to fully cure the immersed polycarbosilane to obtain a gradient resin-based composite material.
[0053] Step 8. Use a single-sided muffle furnace heating method (such as Figure 1 As shown in the figure, the silicon carbide fiber side of the gradient resin-based composite material is heated, and the heating temperature of the single-sided muffle furnace is 900°C for 1 hour. The ceramic precursor on the surface is completely ceramicized, and the ceramic precursor inside is gradient ceramicized, thereby preparing a ceramic-hybrid resin-based gradient heat-insulating integrated composite material.
[0054] like Figure 2 As shown, the ceramic-hybrid resin-based gradient heat-insulating integrated composite material comprises a silicon-containing ceramic matrix 1, silicon carbide fibers 2, a ceramic / resin gradient matrix 3, quartz fibers 4, and an organosilicon hybrid resin matrix 5. The composite material has silicon carbide fibers 2 and quartz fibers 4 distributed in the organosilicon hybrid resin matrix 5, and the content of silicon carbide fibers 2 decreases from the side close to the heat source to the side far from the heat source, and the content of quartz fibers 4 increases, and a silicon-containing ceramic matrix 1 is provided on the surface close to the heat source, and a ceramic / resin gradient matrix 3 is provided inside.
[0055] Example 2
[0056] Step 1. Selecting organosilicon hybrid epoxy resin as the resin matrix raw material, wherein the organosilicon hybrid epoxy resin is prepared according to patent ZL201010134072.7.
[0057] Step 2. Ethyl acetate is selected as the pore-forming solvent, and its volume content accounts for 30% of the total volume of the resin and the pore-forming solvent.
[0058] Step 3. Select a fiber preform of a silicon carbide-quartz gradient orthogonal three-way braided structure as a reinforcement. The silicon carbide fiber-quartz fiber gradient structure consists of a silicon carbide fiber layer, an intermediate transition layer containing both silicon carbide fiber and quartz fiber, and a quartz fiber layer. The volume percentage of the silicon carbide fiber layer decreases in a proportional gradient from 98% to 2% in the thickness direction. At the same time, the volume percentage of the quartz fiber layer increases in a proportional gradient from 2% to 98% in the thickness direction. And the gradient of the reduction in the volume fraction of the silicon carbide fiber layer is the same as the gradient of the increase in the volume fraction of the quartz fiber layer.
[0059] Step 4: Using alternating vacuum-assisted RTM process, setting the vacuum value to -0.09 MPa, the alternating amplitude to 7%, the alternating frequency to 0.4 Hz, and injecting resin into the fiber preform.
[0060] Step 5. Use the alternating temperature curing process to cure the resin, set the curing temperature to 80°C, the alternating temperature amplitude to 2%, the alternating frequency to 0.06Hz, and the curing time to 30h. After curing, a porous resin-based composite material is obtained.
[0061] Step 6. Select polysilazane as the silicon-containing ceramic precursor, expose the surface of the silicon carbide fiber side of the porous resin-based composite material, seal the other surfaces with a vacuum bag, place it in a closed container, and use an alternating pressure impregnation process to impregnate the polysilazane into the porous resin-based composite material. The pressure value of the alternating pressure impregnation is 2.5MPa, the alternating amplitude is 7% of the set pressure value, the alternating frequency is 0.7Hz, and the impregnation time is 15h.
[0062] Step 7. Set the curing temperature to 120° C. and the curing time to 9 h to fully cure the immersed polysilazane to obtain a gradient resin-based composite material.
[0063] Step 8. Heat the silicon carbide fiber side of the gradient resin-based composite material using a single-sided muffle furnace heating method, the single-sided muffle furnace heating temperature is 1050°C, and the heating time is 1.5 hours. The surface ceramic precursor is completely ceramicized, and the internal ceramic precursor is gradient ceramicized, thereby preparing a ceramic-hybrid resin-based gradient heat-insulating integrated composite material.
[0064] Example 3
[0065] Step 1. Select an organosilicon hybrid polyimide resin as a resin matrix raw material, and the organosilicon hybrid polyimide resin is prepared according to patent ZL201811097472.8.
[0066] Step 2. Isopropyl alcohol is selected as the pore-forming solvent, and its volume content accounts for 35% of the total volume of the resin and the pore-forming solvent.
[0067] Step 3. Select a fiber preform of a silicon carbide-quartz gradient three-dimensional four-way braided structure as a reinforcement. The silicon carbide fiber-quartz fiber gradient structure consists of a silicon carbide fiber layer, an intermediate transition layer containing both silicon carbide fiber and quartz fiber, and a quartz fiber layer. The volume percentage of the silicon carbide fiber layer decreases in a proportional gradient from 100% to 0% in the thickness direction. At the same time, the volume percentage of the quartz fiber layer increases in a proportional gradient from 0% to 100% in the thickness direction. And the gradient of the reduction in the volume fraction of the silicon carbide fiber layer is the same as the gradient of the increase in the volume fraction of the quartz fiber layer.
[0068] Step 4: Using the alternating vacuum assisted RTM process, the vacuum value is set to -0.95 MPa, the alternating amplitude is set to 9%, and the alternating frequency is set to 0.6 Hz. Resin is injected into the fiber preform.
[0069] Step 5. Use the alternating temperature curing process to cure the resin, set the curing temperature to 85°C, the alternating temperature amplitude to 3% of the set curing temperature value, and the alternating frequency to 0.08 Hz. The curing time is 36 hours. After curing, a porous resin-based composite material is obtained.
[0070] Step 6. Select polysiloxane as the silicon-containing ceramic precursor, expose the surface of the silicon carbide fiber side of the porous resin-based composite material, seal the other surfaces with a vacuum bag, place it in a closed container, and use an alternating pressure impregnation process to impregnate the polysiloxane into the porous resin-based composite material. The pressure value of the alternating pressure impregnation is 3MPa, the alternating amplitude is 10% of the set pressure value, the alternating frequency is 1.0Hz, and the impregnation time is 20h.
[0071] Step 7. Set the curing temperature to 130° C. and the curing time to 12 h to fully cure the immersed polysiloxane to obtain a gradient resin-based composite material.
[0072] Step 8. Heat the silicon carbide fiber side of the gradient resin-based composite material using a single-sided muffle furnace heating method, the single-sided muffle furnace heating temperature is 1200°C, and the heating time is 2 hours. The surface ceramic precursor is completely ceramicized, and the internal ceramic precursor is gradient ceramicized, thereby preparing a ceramic-hybrid resin-based gradient heat-insulating integrated composite material.
[0073] Comparative Example 1
[0074] Step 1. Select an organosilicon hybrid phenolic resin as a resin matrix raw material, and the organosilicon hybrid phenolic resin is prepared according to patent ZL201911266938.7.
[0075] Step 2. Ethanol is selected as the pore-forming solvent, and its volume content accounts for 25% of the total volume of the resin and the pore-forming solvent.
[0076] Step 3. Select a fiber preform of a silicon carbide 2.5D braided structure as a reinforcement.
[0077] Step 4: Using alternating vacuum-assisted RTM process, setting the vacuum value to -0.08 MPa, the alternating amplitude to 4%, the alternating frequency to 0.2 Hz, and injecting resin into the fiber preform.
[0078] Step 5. Use the alternating temperature curing process to cure the resin, set the curing temperature to 75°C, the alternating temperature amplitude to 1% of the set curing temperature value, and the alternating frequency to 0.02 Hz. The curing time is 24 hours. After curing, a porous resin-based composite material is obtained.
[0079] Step 6. Select polycarbosilane as the silicon-containing ceramic precursor, expose the surface of the silicon carbide fiber side of the porous resin-based composite material, seal the other surfaces with a vacuum bag, place it in a closed container, and use an alternating pressure impregnation process to impregnate the polycarbosilane into the porous resin-based composite material. The pressure value of the alternating pressure impregnation is 2MPa, the alternating amplitude is 2% of the set pressure value, the alternating frequency is 0.2Hz, and the impregnation time is 10h.
[0080] Step 7. Set the curing temperature to 110° C. and the curing time to 6 h to fully cure the immersed polycarbosilane to obtain a gradient resin-based composite material.
[0081] Step 8. The silicon carbide fiber side of the gradient resin-based composite material is heated by a single-sided muffle furnace heating method, the single-sided muffle furnace heating temperature is 900° C., and the heating time is 1 hour. The surface ceramic precursor is completely ceramicized, and the internal ceramic precursor is gradient ceramicized, thereby preparing a composite material.
[0082] Comparative Example 2
[0083] Step 1. Selecting organosilicon hybrid epoxy resin as the resin matrix raw material, wherein the organosilicon hybrid epoxy resin is prepared according to patent ZL201010134072.7.
[0084] Step 2. Ethyl acetate is selected as the pore-forming solvent, and its volume content accounts for 30% of the total volume of the resin and the pore-forming solvent.
[0085] Step 3. Select a fiber preform of a silicon carbide-quartz gradient orthogonal three-way braided structure as a reinforcement. The silicon carbide fiber-quartz fiber gradient structure consists of a silicon carbide fiber layer, an intermediate transition layer containing both silicon carbide fiber and quartz fiber, and a quartz fiber layer. The volume percentage of the silicon carbide fiber layer decreases in a proportional gradient from 98% to 2% in the thickness direction. At the same time, the volume percentage of the quartz fiber layer increases in a proportional gradient from 2% to 98% in the thickness direction. And the gradient of the reduction in the volume fraction of the silicon carbide fiber layer is the same as the gradient of the increase in the volume fraction of the quartz fiber layer.
[0086] Step 4: Using alternating vacuum-assisted RTM process, setting the vacuum value to -0.09 MPa, the alternating amplitude to 7%, the alternating frequency to 0.4 Hz, and injecting resin into the fiber preform.
[0087] Step 5. Use the alternating temperature curing process to cure the resin, set the curing temperature to 80°C, the alternating temperature amplitude to 2%, the alternating frequency to 0.06Hz, and the curing time to 30h. After curing, a porous resin-based composite material is obtained.
[0088] Comparative Example 3
[0089] Step 1. Select an organosilicon hybrid polyimide resin as a resin matrix raw material, and the organosilicon hybrid polyimide resin is prepared according to patent ZL201811097472.8.
[0090] Step 2. Isopropyl alcohol is selected as the pore-forming solvent, and its volume content accounts for 35% of the total volume of the resin and the pore-forming solvent.
[0091] Step 3. Select a fiber preform of a silicon carbide-quartz gradient three-dimensional four-way braided structure as a reinforcement. The silicon carbide fiber-quartz fiber gradient structure consists of a silicon carbide fiber layer, an intermediate transition layer containing both silicon carbide fiber and quartz fiber, and a quartz fiber layer. The volume percentage of the silicon carbide fiber layer decreases in a proportional gradient from 100% to 0% in the thickness direction. At the same time, the volume percentage of the quartz fiber layer increases in a proportional gradient from 0% to 100% in the thickness direction. And the gradient of the reduction in the volume fraction of the silicon carbide fiber layer is the same as the gradient of the increase in the volume fraction of the quartz fiber layer.
[0092] Step 4: Using the alternating vacuum assisted RTM process, the vacuum value is set to -0.95 MPa, the alternating amplitude is set to 9%, and the alternating frequency is set to 0.6 Hz. Resin is injected into the fiber preform.
[0093] Step 5. Use the alternating temperature curing process to cure the resin, set the curing temperature to 85°C, the alternating temperature amplitude to 3% of the set curing temperature value, and the alternating frequency to 0.08 Hz. The curing time is 36 hours. After curing, a porous resin-based composite material is obtained.
[0094] Step 6. Select polysiloxane as the silicon-containing ceramic precursor, expose the surface of the silicon carbide fiber side of the porous resin-based composite material, seal the other surfaces with a vacuum bag, place it in a sealed container, and use a pressure impregnation process to impregnate the polysiloxane into the porous resin-based composite material. The pressure value of the pressure impregnation is 3MPa and the impregnation time is 20h.
[0095] Step 7. Set the curing temperature to 130° C. and the curing time to 12 h to fully cure the immersed polysiloxane to obtain a gradient resin-based composite material.
[0096] Step 8. Heat the silicon carbide fiber side of the gradient resin-based composite material using a single-sided muffle furnace heating method, the single-sided muffle furnace heating temperature is 1200° C., and the heating time is 2 hours. The surface ceramic precursor is completely ceramicized, and the internal ceramic precursor is gradient ceramicized, thereby preparing a composite material.
[0097] Appendix Description
[0098] Table 1 is a summary of the properties of the ceramic-hybrid resin-based gradient thermal insulation integrated composite materials obtained in Examples 1-3 and the composite materials obtained in Comparative Examples 1-3, wherein the density test adopts the GB 1463-2005 method, the thermal conductivity test adopts the GBT10295-2008 method, and the line ablation rate test adopts the GJB 323B-2018 method.
[0099] Table 1
[0100]
[0101] By comparing Example 1 and Comparative Example 1, it can be found that designing the fiber preform as a silicon carbide-quartz fiber gradient woven structure can greatly reduce the thermal conductivity of the material without affecting the ablation resistance compared to the pure silicon carbide fiber woven structure.
[0102] By comparing Example 2 and Comparative Example 2, it can be found that the ceramic-hybrid resin-based gradient thermal insulation integrated composite material has more excellent ablation resistance than the porous resin composite material.
[0103] By comparing Example 3 and Comparative Example 3, it can be found that the use of alternating pressure impregnation is more beneficial to the ablation resistance of the material than fixed pressure impregnation.
[0104] The ceramic-hybrid resin-based gradient heat-insulating integrated composite material prepared by the present invention can have both the ablation resistance of the ceramic-based composite material and the heat insulation performance of the resin-based composite material, and is applied to thermal protection materials for aerospace vehicles.
[0105] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a ceramic-hybrid resin-based gradient heat-insulating integrated composite material, characterized in that: Injecting an organosilicon hybrid resin added with a pore-forming solvent into a fiber preform of a silicon carbide-quartz gradient woven structure, curing to obtain a porous resin-based composite material, impregnating a silicon-containing ceramic precursor from the silicon carbide fiber side of the porous resin-based composite material, curing to obtain a gradient resin-based composite material, and heating the silicon carbide fiber side of the gradient resin-based composite material to prepare a ceramic-hybrid resin-based gradient heat-insulating integrated composite material; The silicon carbide-quartz gradient braided structure is composed of a silicon carbide fiber layer, an intermediate transition layer containing silicon carbide fibers and quartz fibers, and a quartz fiber layer. The braided structure forms include a 2.5D braided structure, an orthogonal three-way braided structure, and a three-dimensional four-way braided structure. The volume percentage of the silicon carbide fiber layer decreases from 95% to 100% to 5% to 0% in a proportional gradient along the thickness direction. At the same time, the volume percentage of the quartz fiber layer increases from 5% to 0% to 95% to 100% in a proportional gradient along the thickness direction, and the gradient of the decrease in the volume percentage of the silicon carbide fiber layer is the same as the gradient of the increase in the volume percentage of the quartz fiber layer.
2. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 1, characterized in that: The organosilicon hybrid resin includes organosilicon hybrid phenolic resin, organosilicon hybrid epoxy resin and organosilicon hybrid polyimide resin.
3. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 1, characterized in that: The types of pore-forming solvents include ethanol, ethyl acetate, and isopropanol; The volume of the pore-forming solvent accounts for 25% to 35% of the total volume of the organosilicon hybrid resin and the pore-forming solvent.
4. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 1, characterized in that: Through the alternating vacuum-assisted RTM process, the organosilicon hybrid resin added with a pore-forming solvent is injected into the fiber preform of the silicon carbide-quartz gradient woven structure, and the injected resin is cured through the alternating temperature curing process to obtain a porous resin-based composite material.
5. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 4, characterized in that: In the alternating vacuum-assisted RTM process, the internal pressure of the resin container is 0.2 to 1.0 MPa, the set vacuum value is -0.08 to -0.95 MPa, the alternating amplitude is 4% to 9% of the set vacuum value, and the alternating frequency is 0.2 to 0.6 Hz; In the alternating temperature curing process, the curing temperature is set at 75-85° C., the alternating temperature amplitude is 1%-3% of the set curing temperature value, the alternating frequency is 0.02-0.08 Hz, and the curing time is 24-36 hours.
6. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 1, characterized in that: The specific process of infiltrating the silicon-containing ceramic precursor from the silicon carbide fiber side of the porous resin-based composite material includes the following steps: S1: The surface of the silicon carbide fiber side of the porous resin-based composite material is exposed, and the other surfaces are sealed with a vacuum bag, placed in a closed container, and the silicon-containing ceramic precursor is impregnated into the porous resin-based composite material by an alternating pressure impregnation process; S2: setting the curing temperature to 110-130° C., fully curing the immersed silicon-containing ceramic precursor for 6-12 hours, and obtaining a gradient resin-based composite material.
7. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 6, characterized in that: The silicon-containing ceramic precursor includes polycarbosilane, polysilazane, and polysiloxane; In the alternating pressure impregnation process, the set pressure value is 2-3 MPa, the alternating amplitude is 2-10% of the set pressure value, the alternating frequency is 0.2-1.0 Hz, and the impregnation time is 10-20 hours.
8. The method for preparing the ceramic-hybrid resin-based gradient heat-insulating integrated composite material according to claim 1, characterized in that: The silicon carbide fiber side of the gradient resin-based composite material is heated by a single-sided muffle furnace heating method. The heating temperature of the single-sided muffle furnace is 900-1200° C. and the heating time is 1-2 hours.
9. A ceramic-hybrid resin-based gradient heat-insulating integrated composite material, characterized in that: The preparation method is described in any one of claims 1 to 8.
Citation Information
Patent Citations
Organic-silicon hybridization epoxy resin as well as preparation method and application thereof
CN101787132A
Organic silicon modified polyimide resin composition and application thereof
CN109517172A
High-strength nanoporous ceramizable ablation-resistant heat-resistant composite material and its preparation method
CN110951210B
High-strength nanoporous ceramizable ablation heatproof composite material and preparation method thereof
CN110951210A
Continuous fiber reinforced thermal protection material and preparation method thereof
CN113997652A